Caracterização dos determinantes da exclusão sanitária dos domicílios rurais brasileiros - Barbara Marques Sales (2018)
There is consensus that are several asymmetries in the provision of sanitation services in Brazil, especially in rural areas. The literature says that the majority of people who do not have access to sanitation have specific aspects, they live in less development regions and low and has low socioeconomic status. Based on the principle of equity present in Law 11.445/2007, identify those who are excluded from adequate sanitation is a great step, of with a view to guiding ways of government acts, organize and plan its budget to attend to this population. In this way, the objective of this work is to characterize the sanitary exclusion in the rural areas in Brazil, and more specifically: i. to explore official databases available for consultation, mainly, information on sanitary issues and discussions about its application; ii. to draw an overview of the temporal evolution of the sanitary situation of Brazilian rural households, based on census data from 1970 to 2010 in terms of water supply, sanitation and solid waste; and iii. to identify the determinants of the sanitary exclusion of the rural population of Brazil, with data from the last Demographic Census (2010), seeking to understand to what extent regional, demographic and socioeconomic aspects influence the existence and reproduction of sanitary exclusion. Thus, an exploratory and critical analysis of the data banks, but also information about rural sanitation in Brazil. Then, variables of interest were selected and structured databases, aiming at characterizing how much more explanatory variable (socioeconomic, demographic and geographic) influences the variable responses (sanitary variables). It was observed that the data currently available in official databases are not sufficient to characterize the sanitary situation of Brazilian rural households satisfactorily. The sanitation deficit in Brazil still significant large and the statistical analyzes indicate that certain groups suffer from sanitary exclusion, among them, households with a household income of less than 1.5 minimum salary, inadequate infrastructure, households have low schooling and are black or indigenous, and is located in the north or northeast of the country are the most likely to be in this group. It cannot be denied that there have been advances in coverage levels, but these have not been sufficient to really guarantee adequate care for the majority of the disadvantaged population and reduce inequalities.